EDUKASI EKONOMI SYARIAH DAN DIGITAL MARKETING PADA PELAKU UMKM DI AGROWISATA PALOH NAGA - Nuraisah; Wirya, Syafira Okta Vionna; Gifari, Muhammad Al; Syarfina, Wahyu (Jurnal Pengabdian Masyarakat Sabangka, 2025)
This community service program aims to provide education about sharia economy and digital marketing to MSMEs and PKK Women in Paloh Naga Agrotourism, Denai Lama Village. The activity was carried out through a lecture and discussion method followed by 20 participants. The material of sharia economics emphasizes the principles of halal and thayyib, justice, transparency, and the implementation of a profit-sharing system. Meanwhile, the digital marketing session teaches the use of social media as a promotion strategy to increase product attractiveness and the number of tourist visits. The results of the activity showed that the participants gained a better understanding and were motivated to implement sharia-based business practices and digital promotions. This program also contributes to increasing the exposure of Paloh Naga Agrotourism through the creation of promotional content. This activity is expected to be able to support the economic empowerment of the community sustainably.